Molecular characterization and association of Leptin receptor polymorphisms with obesity in Malay subjects - Aliya Irshad Sani
Obesity is a major health risk affecting the population at large. Current obesogenic environment and sedentary lifestyle along with susceptible genes predispose individuals to develop obesity. Orexigenic and anorexigenic factors interplay in harmony to maintain weight. Leptin and its receptor play a crucial role in weight maintenance centrally and peripherally. Gene polymorphisms have been reported to have a role in the pathogenesis of obesity, diabetes, metabolic syndrome, hypertension and cancer. This study was conducted to investigate the frequencies of Single Nucleotide Polymorphisms (SNP) in Leptin (LEP) gene (G2548A) and leptin receptor (LEPR) gene (Q223R); and to correlate the SNPs with lipid profile and anthropometric measurements. The association analysis of the obese attributes may provide a baseline data for the obesity genetic and pattern of diversity among Malays. Cross sectional study was conducted among 217 subjects who were selected by convenience sampling with obtaining informed consent. After taking anthropometric measurements, males (n=74) and females (n=149) were grouped into two categories based on the body mass index (BMI) : >30 kg/rrr' as obese (n=94), mean age 39.2 ± 10.0 years) and <25 kg/m'' normal (n=123), mean age 33.6 ± 10. The individuals who were overweight, suffering from liver and renal problems were excluded. Phlebotomy was performed for lipid profile analysis followed by genotyping using Polymerase Chain Reaction Restriction Fragment Length Polymorphism (PCR-RFLP). The significant difference was observed between two groups of BMI in anthropometric measurements and lipid profile except for total cholesterol (p=0.094). In this study the frequencies of different genotypes of LEP G2548A in obese and non-obese were found to be GG (26% vs 19%), GA (39% s 30%) and AA (35% vs 51%) and the A allele (54% vs 65%) was found to be more prevalent. Leptin SNP showed fair association with obesity with p va/ue=0.015. While the frequencies for LEPR Q223R genotype were found to be QQ (22% vs 15%), QR (28% vs 33%) and RR (50% vs 51%) and the R allele (64% vs 68%) was more prevalent but no association observed with obesity based on allelic p va/ue=0.37. In this study there was no association of LEP and LEPR SNPs with lipid profile parameters. The waist circumference and waist hip ratio were found to be higher in QR genotype obese individuals with 99.61 em ± 10.8 and 0.91 cm± 0.08, respectively, compared to QQ and RR genotypes of LEPR polymorphism. The total cholesterol and low density lipoprotein (LDL) were higher in RR genotypic group with values of 6.] 8 ± 1.5 and 4.47 ± 1.28 respectively as compared to other two genotypes. However, binary logistic regression showed no association of polymorphisms with obesity parameters except for AA genotype having reducing effect on TG (OR, 0.40; 95% CI, 0.17-0.94; P value=0.04)]. In conclusion, based on the anthropometric measurements and lipid profile, the polymorphism of leptin and leptin receptor did not attribute to obesity. However further evidence can be gained by measuring leptin levels and other polymorphisms of these genes as limitations of this study.